Solidarity in an Eco-Relational Paradigm for Peace and Justice? - Svigelj, Melissa (In Factis Pax: Journal of Peace Education and Social Justice, 2025)
Abstract The term solidarity has inspired many definitions, levels, forms, interpretations, and material enactments. In general, traditional Western understandings of solidarity have emphasized the intersubjective relations that emerge during shared experiences of confronting interlocking systems of domination. However, an emphasis on subjectivity and the body and mind of the conscious individual in interaction with the body and mind of another has constrained imagination and encouraged an unquestioning acceptance of the human as the most significant and perhaps only species or entity capable or worthy of solidarity efforts. Rather than advocating for "humanization" while engaging in acts of solidarity for justice and peace, as if that figurative metamorphosis by anyone or anything inherently results in endorsements of their worthiness for relief, we must honestly confront the everyday, often unquestioned violence of anthropocentrism--the belief that human beings are the central or most important entity on the planet. Rather than offering sustainable peace or justice, solidarity that prioritizes human exceptionalism and domination can exacerbate the violence of human-created ecological crises. Drawing from theoretical and practical discourse across disciplines, this conceptual essay explores why and what sort of paradigmatic and epistemological shifts for an eco-relational solidarity are necessary for peace and justice education and studies. As Indigenous philosophies based on relational ontologies have long demonstrated, reconsiderations of solidarity’s Western traditional meanings and practices must include acknowledging the profound interconnectedness of all beings. Solidarity in an eco-relational paradigm anchors us in systems thinking and helps us recognize the infinite number of interconnections we share beyond those with fellow humans. The development and introduction of an eco-relational solidarity (not charity) in peace and justice education and studies can dismantle human exceptionalism and domination prominent in the creation of the climate emergency and manifest broader epistemologies and praxes that prioritize more-than-human solidarity for peace, justice, and addressing the climate crisis.